2018
DOI: 10.1159/000493410
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Post-Surgical Parenteral Nutrition on Patients with Gastric Cancer

Abstract: Background/Aims: In this study, we investigated the effect of post-surgical parenteral nutrition on patients with gastric cancer (GC) and its possible mechanism. Methods: A total of 108 patients were invited to assess for eligibility and 28 patients were excluded. The eighty patients were randomized to either a study group (1 L peripheral intravenous nutrition, 700 kcal) or a control group (1 L isotonic electrolyte solution). Parenteral nutrition was started on day 1 post-surgery and maintained for 4-8 days. L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…9. Summary and outlook: Improving nutritional support for patients undergoing major gastrointestinal surgery Improved awareness of the adverse impact of poor nutritional status as well as metabolic stress on patients undergoing major gastrointestinal surgery and the benefits of timely and appropriate nutrition support, which include shorter hospital stay, fewer complications and improved patient wellbeing, is warranted [dataset [57,59]]. Implementation of ERAS recommendations for perioperative nutritional support can help to optimize patient outcomes [dataset [34]].…”
Section: Algorithm To Deliver Ppn In the Context Of Erasmentioning
confidence: 99%
“…9. Summary and outlook: Improving nutritional support for patients undergoing major gastrointestinal surgery Improved awareness of the adverse impact of poor nutritional status as well as metabolic stress on patients undergoing major gastrointestinal surgery and the benefits of timely and appropriate nutrition support, which include shorter hospital stay, fewer complications and improved patient wellbeing, is warranted [dataset [57,59]]. Implementation of ERAS recommendations for perioperative nutritional support can help to optimize patient outcomes [dataset [34]].…”
Section: Algorithm To Deliver Ppn In the Context Of Erasmentioning
confidence: 99%
“…Serum PAB is an effective tool for evaluating malnourished patients [ 31 ]. It has been reported that the level of PAB in the study group was significantly higher than that in the control group when parenteral nutrition was given after the gastric cancer surgery [ 32 ]. CER is a kind of ferrous oxidase in mammalian plasma and plays a vital role in the iron metabolism [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Parenteral nutrition may be the only option especially for patients who are not suitable for enteral feeding. There are studies suggesting that parenteral nutrition can significantly improve patients' nutritional and psychological status, quality of life and immune functions (17). In addition, a study in an elderly patients undergoing surgery for gastric cancer showed that the combination of enteral and parenteral nutrition is superior to early enteral nutrition or total parenteral nutrition in promoting immune recovery (18).…”
Section: Discussionmentioning
confidence: 99%